Strategy of Permadani Dakwah Institution in Guiding Qur'an Village Program in Bandar Setia Village, Percut Sei Tuan District - Soraya, Siti Fitria; Madya, Efi Brata (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2025)
The Permadani Dakwah Institute (Association of Qur'anic Dakwah Youth), is an organization that focuses on building the young generation in an educational journey based on the Qur'an. This study aims to analyze the strategies carried out by the Permadani Dakwah Institute within the framework of the Qur'an Village development program in Bandar Setia Village, Percut Sei Tuan District. This study uses a qualitative descriptive approach, namely data obtained from in-depth interviews with the head of the institution, foundation, and teachers in program management. The results of the study indicate challenges and obstacles, such as the minimal role of youth and lack of support from the local government. The Qur'anic Village Managers overcome these obstacles by collaborating with the community, parents and the local government by organizing various dakwah programs, such as tafsir studies, dhikr, tasbih prayers, teenage dakwah overnight stays, children's post-maghrib studies and Permadani sharing. The strategies used have proven to be effective and efficient in building the Qur'anic generation in the Qur'anic Village. Lembaga Dakwah Permadani (Persatuan Pemuda Dakwah qur’ani), merupakan organisasi yang berkonsentrasi membangun generasi muda dalam menempuh pendidikan berlandaskan Al-Qur'an Penelitian ini bertujuan untuk menganalisis strategi yang dilakukan oleh Lembaga Dakwah Permadani dengan rangka pembinaan program Kampung Qur'an di Desa Bandar Setia, Kecamatan Percut Sei Tuan. Penelitian ini menggunakan pendekatan deskriptif kualitatif, yaitu data yang diperoleh dari wawancara mendalam terhadap ketua lembaga, yayasan, dan pengajar dalam pengelola program. Hasil penelitian menunjukkan terdapat adanya tantangan maupun hambatan, seperti minimnya peran pemuda dan kurangnya support dari pemerintah setempat. Para Pengelola Kampung Qur’ani mengatasi hambatan tersebut dengan melakukan kolaborasi ke masyarakat, orang tua dan Pihak pemerintah setempat dengan menyelenggarakan berbagai program dakwah, seperti pengajian tafsir, dzikir, sholat tasbih, mabit dakwah remaja, pengajian ba’da maghrib anak-anak dan Permadani berbagi. Strategi yang digunakan teruji efektif dan efisien dalam membangun generasi Qur’ani di Kampung Qur'an.